Gairah Tabu: Mengimajinasikan Kembali Indonesia Melalui Pornografi - Smith, Malcolm Le (Retorik: Jurnal Ilmu Humaniora, 2025)
This essay draws a parallel between the Indonesian Romance industry and Pornography industry; and Indonesian “legacy” media (print, radio and television news) and social media. In the classic romance narrative, true love can only be found when the heteronormative moral order has been restored. In pornography, there are always two players—the voyeur and the narcissist, who are locked in a feedback loop of transgression and pleasure. The essay charts how pornography played an important role in the development of internet technologies, not only through the injection of capital into innovation, but also in the way users subjectively engaged with these images. As human interaction and political discourse increasingly shifts online, it is timely to consider how online technologies determine those interactions.